Pickford 50th Anniversary 1903 - Pickford, Joel:::::::::
The photograph was taken to celebrate the 50th wedding anniversary of Oliver and Mary Ann Pickford on October 22, 1903; back row, standing L-R: Olive Pickford Matheisen, 39, unknown woman, possibly a common law wife of John Pickford, George Matheisen, 44 (husband of Olive), John Pickford, 45, Lottie Pickford Kohler, 48, Georgie Pickford (son of Thomas Pickford), 17, George Kohler (husband of Lottie), 50, Charles Swett (husband of Hattie), 56, Thomas Pickford, 47, Hattie Pickford Swett, 41, Grace Whitney Pickford, 38 (wife of Thomas Pickford), 45, George Pickford, 42 (Rollin's grandfather), Ida Studer Pickford, 37 (Rollin's grandmother and George's wife); front row, seated L-R: Vernal Pickford, 6 months (infant son of Job Pickford), Job Pickford, 33 (holding his son, Vernal), unknown man, possibly fiancé or spouse of Lottie Matheisen, May Sullivan Pickford, 33 (Job's wife), Lottie Matheisen, 18 (daughter of Olive Pickford Matheisen), Oliver Pickford (Rollin's great grandfather), 74, William Pickford, 11 (Rollin's uncle), Mary Ann Pickford, 76 (Rollin's great grandmother), Winnie Swett, 18 (Hattie Pickford Swett's daughter), Mary E. Pickford, 27 (Ernie Pickford's wife), 27, Ernie Pickford, 28, Rollin A. Pickford Sr., 16 (the artist's father).